Deleterious Effect of RAS and Evolutionary High-risk TP53 Double Mutation in Colorectal Liver Metastases. Issue 5 (May 2019) - Chun, Yun Shin; Passot, Guillaume; Yamashita, Suguru; Nusrat, Maliha; Katsonis, Panagiotis; Loree, Jonathan M.; Conrad, Claudius; Tzeng, Ching-Wei D.; Xiao, Lianchun; Aloia, Thomas A.; Eng, Cathy; Kopetz, Scott E.; et al.
Abstract : Objective: To assess the impact of somatic gene mutations on survival among patients undergoing resection of colorectal liver metastases (CLM). Background: Patients undergoing CLM resection have heterogeneous outcomes, and accurate risk stratification is necessary to optimize patient selection for surgery. Methods: Next-generation sequencing of 50 cancer-related genes was performed from primary tumors and/or liver metastases in 401 patients undergoing CLM resection. Missense TP53 mutations were classified by the evolutionary action score (EAp53)—a novel approach that dichotomizes mutations as low or high risk. Results: The most frequent somatic gene mutations were TP53 (65.6%), followed by KRAS (48.1%) and APC (47.4%). Double mutation in RAS / TP53, identified in 31.4% of patients, was correlated with primary tumor location in the right colon ( P = 0.006). On multivariable analysis, RAS/TP53 double mutation was an independent predictor of shorter overall survival (hazard ratio 2.62, 95% confidence interval 1.41–4.87, P = 0.002). In patients with co-mutated RAS, EAp53 high-risk mutations were associated with shorter 5-year overall survival of 12.2%, compared with 55.7% for TP53 wild type ( P < 0.001). The negative prognostic effects of RAS and TP53 mutations were limited to tumors harboring mutations in both genes. Conclusions: Concomitant RAS and TP53 mutations are associated with decreased survival after CLM resection. A high EAp53 predicts a subset of patients with worse prognosis. These preliminary analyses suggest that surgical resection of liver metastases should be carefully considered in this subset of patients.